Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/chem.201605029
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a Polyene Cyclization Cascade for the Total Synthesis of (−)‐Cyclosmenospongine

Abstract: We report a full account on the development of a unique cationic polyene cyclization for the total synthesis of the tetracyclic meroterpenoid (−)‐cyclosmenospongine. A highly convergent three‐component coupling strategy enabled rapid access to individual cyclization precursors that were tested for their reactivity. The successful transformation generates three rings and sets four consecutive stereocenters in a single operation proceeding in a highly efficient manner to give exclusively the trans‐decalin framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 90 publications
(67 reference statements)
1
17
0
Order By: Relevance
“…In this type of natural product, it is common to determine the molecular constitution and the relative stereochemistry, but the absolute configuration sometimes remains unassigned until the total synthesis is performed, either starting from an enantiomerically pure natural compound, or using stereocontrolled reactions. This is the case for (+)-strongylin A ( 137 ) [ 69 ], (+)-aureol ( 131 ) [ 70 ], and (−)-cyclosmenospongine ( 138 ) [ 71 ], which have been recently reported ( Figure 19 ).…”
Section: Meroterpenoids With Open-chain and Cyclic Sesquiterpenoidsupporting
confidence: 53%
“…In this type of natural product, it is common to determine the molecular constitution and the relative stereochemistry, but the absolute configuration sometimes remains unassigned until the total synthesis is performed, either starting from an enantiomerically pure natural compound, or using stereocontrolled reactions. This is the case for (+)-strongylin A ( 137 ) [ 69 ], (+)-aureol ( 131 ) [ 70 ], and (−)-cyclosmenospongine ( 138 ) [ 71 ], which have been recently reported ( Figure 19 ).…”
Section: Meroterpenoids With Open-chain and Cyclic Sesquiterpenoidsupporting
confidence: 53%
“…446 In 2018, the Maulide group demonstrated that by using thiouronium ylides, in which the cationic functionality is stabilized, it was possible to achieve (3 + 2)-cycloadditions at room temperature under very mild conditions, generating dihydrothiophenes ( 755 ) following elimination of an amine (Scheme 144b). 447 Alternative approaches have been employed in natural product syntheses by Trauner (Scheme 144c) 448 and Magauer (Scheme 144d), 449 as a strategy for syn -dialkylation of alkenes, because the generated tetrahydrothiophenes can be desulfurized through the use of Raney Ni. The latter example makes use of high pressure conditions to promote productive reactivity, and both examples employ highly polar solvents.…”
Section: Sulfur Ylidesmentioning
confidence: 99%
“…Owing to their unique structural features coupled with their attractive biological activities, these natural products are exceptionally intriguing and timely targets for total synthesis. Total syntheses of unnatural (–)‐ 1 , natural (–)‐ 2 , and natural (+)‐ 4 have been reported; however, the total synthesis of 3 has not been reported to date . In this study, we describe the unified total syntheses of compounds 1 – 4 , all with the natural absolute configurations.…”
Section: Introductionmentioning
confidence: 99%